Testing the global banking glut hypothesis - Karlo Kauko; Maria Teresa Punzi (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2015)
This paper presents VAR results on the recent economic history of the USand focuses on the dependence of US macro financial variables on international capital flows. Both gross and net flows are included in the analysis. The results indicate that cross-border funding has affected the build-up in the US housing market irrespective of how these flows are defined and measured. Both the savings glut hypothesis and the banking glut hypothesis are supported by these findings. However, net banking flows appear to explain the higher volatility in the increase in house prices as well as the mortgage loan boom.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: F32; F33; F34; 330; Global Banking Glut; Global Savings Glut; Cross-Border Banking Transactions; House Prices; Mortgage Loans; VAR model